Reconstruction of the Metabolic Potential of Acidophilic Sideroxydans Strains from the Metagenome of an Microaerophilic Enrichment Culture of Acidophilic Iron-Oxidizing Bacteria from a Pilot Plant for the Treatment of Acid Mine Drainage Reveals Metabolic Versatility and Adaptation to Life at Low pH - Mühling, Martin; Poehlein, Anja; Stuhr, Anna; Voitel, Matthias; Daniel, Rolf; Schlömann, Michael (Frontiers in Microbiology, 2016)
Bacterial community analyses of samples from a pilot plant for the treatment of acid mine drainage (AMD) from the lignite-mining district in Lusatia (East Germany) had previously demonstrated the dominance of two groups of acidophilic iron oxidizers: the novel candidate genus "Ferrovum" and a group comprising Gallionella-like strains. Since pure culture had proven difficult, previous studies have used genome analyses of co-cultures consisting of “Ferrovum” and a strain of the heterotrophic acidophile Acidiphilium in order to obtain insight into the life style of these novel bacteria. Here we report on attempts to undertake a similar study on Gallionella-like acidophiles from AMD. Isolates belonging to the family Gallionellaceae are still restricted to the microaerophilic and neutrophilic iron oxidizers Sideroxydans and Gallionella. Availability of genomic or metagenomic sequence data of acidophilic strains of these genera should, therefore, be relevant for defining adaptive strategies in pH homeostasis. This is particularly the case since complete genome sequences of the neutrophilic strains G. capsiferriformans ES-2 and S. lithotrophicus ES-1 permit the direct comparison of the metabolic capacity of neutrophilic and acidophilic members of the same genus and, thus, the detection of biochemical features that are specific to acidophilic strains to support life under acidic conditions. Isolation attempts undertaken in this study resulted in the microaerophilic enrichment culture ADE-12-1 which, based on 16S rRNA gene sequence analysis, consisted of at least three to four distinct Gallionellaceae strains that appear to be closely related to the neutrophilic iron oxidizer S. lithotrophicus ES-1. Key hypotheses inferred from the metabolic reconstruction of the metagenomic sequence data of these acidophilic Sideroxydans strains include the putative role of urea hydrolysis, formate oxidation and cyanophycin decarboxylation in pH homeostasis.